2015
DOI: 10.1155/2015/653419
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Dermatophytic Infection and the Spectrum of Dermatophytes in Patients Attending a Tertiary Hospital in Addis Ababa, Ethiopia

Abstract: Background. Dermatophytosis is common worldwide and continues to increase. Objective. This study was undertaken to determine the prevalence of dermatophytosis and the spectrum of ringworm fungi in patients attending a tertiary hospital. Methods. Samples were collected from 305 patients. A portion of each sample was examined microscopically and the remaining portion of each sample was cultured onto plates of Sabouraud's dextrose agar containing chloramphenicol with and without cycloheximide. Dermatophyte isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

17
68
3
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(93 citation statements)
references
References 26 publications
17
68
3
2
Order By: Relevance
“…In the present study, direct microscopy positivity rate is 133/318(41.8%) and culture positivity rate is 148/318(46.5 %) ( Table: 1). This was in line with a study conducted in Addis Ababa, Ethiopia, 42.6% [9]. This occurrence is due to that; Ethiopia is a tropical country with wet humid climate, large population size, and low socioeconomic status and this is supported by other studies conducted on dermatophytosis etiologies and risk factors [9,15,16,34].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In the present study, direct microscopy positivity rate is 133/318(41.8%) and culture positivity rate is 148/318(46.5 %) ( Table: 1). This was in line with a study conducted in Addis Ababa, Ethiopia, 42.6% [9]. This occurrence is due to that; Ethiopia is a tropical country with wet humid climate, large population size, and low socioeconomic status and this is supported by other studies conducted on dermatophytosis etiologies and risk factors [9,15,16,34].…”
Section: Discussionsupporting
confidence: 90%
“…), overcrowding, environmental hygiene culture, awareness to dermatophytes, age of individuals, hygiene and socioeconomic conditions have been described as major factors for these variations of dermatophyte epidemiology [4,5,6,7]. Childrens between the ages of 4 and 16 years are more at risk due to more contact to different sources and inadequate amount of fungi-inhibiting fatty acids synthesized predisposed them to dermatophytic infections [8,9,10]. Now days, there are about 40 known species in the genera of dermatophytes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study showed that males are infected more when compared to females with a male female ratio of 2:1 (Table 3). Meanwhile there are studies which show a higher prevalence of dermatophytic infections in females than males 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Incidences of the prevalence is not only particular to Lagos-Nigeria but is observed in many countries and crowded places in the world. For instance, Lakshmanan et al (2015) reported a high incidence of fungal infection in rural India while Teklebirhan and Bitew (2015) reported a prevalence of 79.4% in 242 sampled cases.…”
mentioning
confidence: 99%